2006
DOI: 10.1113/jphysiol.2006.106740
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen and weight loss decrease isoproterenol‐induced Fos immunoreactivity and angiotensin type 1 mRNA in the subfornical organ of female rats

Abstract: Studies from our laboratory and others show that oestrogen reduces angiotensin II (Ang II)-induced water intake by ovariectomized rats. Elimination of endogenous oestrogen by ovariectomy causes weight gain that can be reversed or prevented by oestrogen replacement. Changes in body weight modify cardiovascular responses to Ang II but whether such changes have similar effects on central and behavioural responses to Ang II is unknown. The goal of this study was to evaluate the contributions of oestrogen and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
63
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 51 publications
14
63
1
Order By: Relevance
“…The age-adjusted body weight in ad libitum fed rats is significantly greater in Wistar rats than in Fisher 344 rats [27]. Although we did not measure physical activity or basal metabolism in the previous or present study, exogenous administration of estrogen and/or ghrelin has also been reported to alter food intake and consequently body weight in rats [26,28].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The age-adjusted body weight in ad libitum fed rats is significantly greater in Wistar rats than in Fisher 344 rats [27]. Although we did not measure physical activity or basal metabolism in the previous or present study, exogenous administration of estrogen and/or ghrelin has also been reported to alter food intake and consequently body weight in rats [26,28].…”
Section: Discussionmentioning
confidence: 48%
“…The different age of the old subgroup and species of the animal model (13 months old Wistar rats vs 18 months old Fisher 344 rats) could be responsible. It is also possible that body weight affects the target tissue vascular response to estrogen and ghrelin in rats similar to other cardiovascular control functions such as the renin-angiotensin system [26]. The age-adjusted body weight in ad libitum fed rats is significantly greater in Wistar rats than in Fisher 344 rats [27].…”
Section: Discussionmentioning
confidence: 91%
“…The c-fos fragment (original full-length cDNA from T. Curran, St. Jude Children’s Research Hospital, Memphis, TN) was cloned into a TOPO PCR vector (Invitrogen, Carlsbad, CA), linearized with Hind III, and transcribed with T3 RNA polymerase. Pretreatment of slides, hybridization, post-treatment and image analysis were performed as previously described (Krause et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…In fact, accumulating evidence supports the idea that estrogens reduce ‘volemic thirst’ — fluid intake stimulated by activation of the renin–angiotensin system. We and others have reported that, in rats, estrogens attenuate water intake stimulated by isoproterenol [19,20,30,32,61], a β-adrenergic agonist that produces a robust increase in circulating levels of angiotensin II (AngII). Importantly, the reduction of isoproterenol-induced drinking by estradiol-treated ovariectomized rats occurs despite comparable elevations in AngII [30].…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal activation in response to isoproterenol differs in specific central nuclei, depending on whether ovariectomized rats are treated with estradiol [26,31,32]. In this regard, estrogens are highly lipophilic and can easily access estrogen receptors (ERs) located throughout the CNS, particularly in areas involved in body fluid balance [2,24,45,50,51,53,54,59,60,62].…”
Section: Introductionmentioning
confidence: 99%